Aspectos reprodutivos de Anableps anableps (Linnaeus, 1758) (Cyprinodontiformes: Anablepidae) no Estuário Amazônico - Oliveira, Valéria de Albuquerque (Museu Paraense Emilio Goeldi, 2016)
The dissertation was elaborated in the article format. The first article entitled " Reproductive aspects and length-weight relationship of Anableps anableps (Linnaeus , 1758 ) ( Cyprinodontiformes : Anablepidae ) in the Amazon Estuary " provides information on the reproductive biology of A. anableps addressing sex ratio , length-weight relationship , estimate the first sexual maturation and breeding season . This article will be submitted to the Journal of Zoology. The second article " Morphological characterization of the gonads of Anableps anableps females (Linnaeus , 1758 ) ( Cyprinodontiformes : Anablepidae ) in the Amazon estuary " presents a morphological description of the gonads of A. anableps females at the mouth of the Maracanã -PA river. It will be submitted as a scientific journal Neotropical Ichthyology note .